Enhanced degradation of softwood versus hardwood by the white-rot fungus Pycnoporus coccineus. Issue 1 (December 2015) - Couturier, Marie; Navarro, David; Chevret, Didier; Henrissat, Bernard; Piumi, François; Ruiz-Dueñas, Francisco; Martinez, Angel; Grigoriev, Igor; Riley, Robert; Lipzen, Anna; Berrin, Jean-Guy; Master, Emma; et al.
Abstract Background White-rot basidiomycete fungi are potent degraders of plant biomass, with the ability to mineralize all lignocellulose components. Recent comparative genomics studies showed that these fungi use a wide diversity of enzymes for wood degradation. Deeper functional analyses are however necessary to understand the enzymatic mechanisms leading to lignocellulose breakdown. The Polyporale fungusPycnoporus coccineus BRFM310 grows well on both coniferous and deciduous wood. In the present study, we analyzed the early response of the fungus to softwood (pine) and hardwood (aspen) feedstocks and tested the effect of the secreted enzymes on lignocellulose deconstruction. Results Transcriptomic and proteomic analyses revealed thatP. coccineus grown separately on pine and aspen displayed similar sets of transcripts and enzymes implicated in lignin and polysaccharide degradation. In particular, the expression of lignin-targeting oxidoreductases, such as manganese peroxidases, increased upon cultivation on both woods. The sets of enzymes secreted during growth on both pine and aspen were more efficient in saccharide release from pine than from aspen, and characterization of the residual solids revealed polysaccharide conversion on both pine and aspen fiber surfaces. Conclusion The combined analysis of soluble sugars and solid residues showed the suitability ofP. coccineus secreted enzymes for softwood degradation. Analyses of solubilized products and residual surface chemistries of enzyme-treated wood samples pointed to differences in fiber penetration by differentP. coccineus secretomes. Accordingly, beyond the variety of CAZymes identified inP. coccineus genome, transcriptome and secretome, we discuss several parameters such as the abundance of manganese peroxidases and the potential role of cytochrome P450s and pectin degradation on the efficacy of fungi for softwood conversion.